Pedagogical and Didactic Aspects in Sciencie Club for Infants Taught by University Students - Araya Quesada, Yorleny (2024)
This paper presents the systematization of a non-formal educational experience. The aim of this study was to recognize the emerging pedagogical and didactic aspects during a science’s club. The research was qualitative, exploratory, and interpretive. The methodological design was a systematization of 10 sessions of a science´s club for infants. University of Costa Rica students were the facilitators. Observations, interviews, and a focus group were used. The results show pedagogical and didactic theoretical dimensions. The pedagogical aspects refer to the desire to learn and communicate knowledge, satisfaction and concern for teaching. The didactic aspects refer to the motivation to teach through interesting activities through teamwork, with contributions from different disciplines. The conclusions indicate that the experiences of the students favored a process of personal and group training and transformation. Furthermore, the science taught is approached from empirical knowledge of demonstration and experimentation and the importance of communication and reflection for the improvement of non-formal education processes is highlighted.